2010
DOI: 10.3109/00365521.2010.539253
|View full text |Cite
|
Sign up to set email alerts
|

Blood chemistry markers for evaluation of inflammatory activity in Crohn's disease during infliximab therapy

Abstract: Although infliximab ameliorates Crohn's disease symptoms, inflammatory markers are not persistently normalized, indicating a chronic inflammatory condition that may require continued infliximab therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 36 publications
2
16
0
2
Order By: Relevance
“…In a recently published study on 60 IBD patients (34 with CD and 26 with UC), normalization of calprotectin after infliximab or adalimumab induction therapy predicted sustained clinical remission during scheduled maintenance therapy in the majority of patients [30]. A similar decrease of calprotectin after infliximab therapy has been described in several other studies [11,14,31]. Calprotectin and lactoferrin were correlated with endoscopic activity during anti-TNF-α therapy and seemed to be a good marker of MH [11].…”
Section: Calprotectinsupporting
confidence: 49%
See 3 more Smart Citations
“…In a recently published study on 60 IBD patients (34 with CD and 26 with UC), normalization of calprotectin after infliximab or adalimumab induction therapy predicted sustained clinical remission during scheduled maintenance therapy in the majority of patients [30]. A similar decrease of calprotectin after infliximab therapy has been described in several other studies [11,14,31]. Calprotectin and lactoferrin were correlated with endoscopic activity during anti-TNF-α therapy and seemed to be a good marker of MH [11].…”
Section: Calprotectinsupporting
confidence: 49%
“…A series of new biomarkers including nitric oxide, the soluble form of urokinase-type plasminogen activator receptor, ghrelin or endothelin-1 have been examined for assessment of disease activity and response to anti-inflammatory treatment [14]. However, only preliminary data from pilot studies have so far been published.…”
Section: New Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding that suPAR levels in healthy controls were similar to those reported in comparable children (15)(16)(17)(18) imparts validity to the suPAR levels we measured in our patients with forms of CKD. Numerous studies have shown serum suPAR levels to be increased with nonspecific inflammation or immune activation (15)(16)(17)(18)(19)(20)(21)(22)(23). In fact, urokinase plasminogen activator receptor is expressed on various cell types (neutrophils, lymphocytes, monocytes, and endothelial and tumor cells).…”
Section: Discussionmentioning
confidence: 99%